Self-preferencing, Quality Provision, and Welfare in Mobile Application Markets - Xuan Teng (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Platforms often display their products ahead of third-party products in search. Is this due to consumers preferring platform-owned products or platforms engaging in self-preferencing by biasing search towards their own products? What are the welfare implications? I develop a structural model of mobile application markets to identify self-preferencing and quantify its welfare effects, taking into account third-party developers' quality adjustment. A new dataset on app downloads, prices, characteristics, and search rankings is used to estimate the model. Estimates indicate self-preferencing. Simulations show higher consumer welfare and third-party profits without self-preferencing.
Keywords: D12; D83; L13; L86; 330; competition policy; platform design; consumer search; endogenous product choice